Low Genetic Connectivity of Strongly Inbred Ruppia brevipedunculata in Aquaculture Dominated Lagoons (Viet Nam) - Triest, Ludwig; Dierick, Jasper; Phan, Thi Thuy Hang; Luong, Quang Doc; Huy, Nguyen Quang; Sierens, Tim (Frontiers in Conservation Science, 2021)
Lagoonal environments exhibit high levels of instability depending on hydrological, climatic and ecological factors, thereby influencing the distribution and structure of submerged plant communities. Conditions typically fluctuate widely due to the interaction of freshwater from rivers with saltwater from the sea, as well as from aquaculture activities that together influence submerged hydrophyte community spatial and temporal variability depending on plant survival strategies. Ruppia species feature either underwater pollination mediated by an air bubble or by the release of pollen floating at the water surface, the former promoting self-pollination. Tropical Asian Ruppia brevipedunculata Yu & den Hartog was assumed to pollinate below the water surface and identified as a separate lineage among selfed Ruppia taxa. We used 9 nuclear microsatellites to estimate inbreeding levels and connectivity of R. brevipedunculata within a large SE Asian lagoon complex. Ruppia brevipedunculata meadows were strongly inbred as could be derived from the many monomorphic or totally fixed loci for unique alleles in different parts of the lagoon, which appears consistent with selfing behaviour. Those from aquaculture ponds were highly inbred (FIS = 0.620), though less than open lagoon sites that showed nearly total inbreeding (FIS = 0.942). Ruppia brevipedunculata from two major lagoon parts were highly differentiated with spatially structured gene pools and a strong barrier between parts of the lagoon over a 30 km distance. Migration-n analysis indicated unidirectional though limited gene flow and following potential hydrological connectivity. Overall, private alleles under homozygote conditions explained a stronger genetic differentiation of populations situated inside aquaculture ponds than of open lagoon populations. Kinship values were only relevant up to 5 km distance in the open lagoon. Within a confined area of aquaculture ponds featuring dense vegetation in stagnant water, there would be opportunity for mixed pollination, thereby explaining the higher diversity of unique multilocus genotypes of aquaculture pond habitats. Low connectivity prevents gene pools to homogenize however promoted sites with private alleles across the lagoon. Complex hydrodynamic systems and human-made habitats enclosed by physical structures impose barriers for propagule dispersal though may create refugia and contribute to conserving regional genetic diversity.